2019
DOI: 10.1021/acsami.9b04622
|View full text |Cite
|
Sign up to set email alerts
|

Anion Exchange Membranes with Dynamic Redox-Responsive Properties

Abstract: Redox-responsive anion exchange membranes were developed using photoinitiated free-radical polymerization and reversible oxidation and reduction of viologen. The membranes were formulated using poly­(ethylene glycol diacrylate) and diurethane dimethacrylate oligomers, dipentaerythritol penta-/hexa-acrylate cross-linker, photoinitiators, and 4-vinylbenzyl chloride as precursors for functionalization. In the membrane, 4,4′-bipyridine reacted with the 4-vinylbenzyl chloride residues, and subsequently, unreacted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, it was observed that the water uptake of the samples increased as the cycle number increased, which further supported this hypothesis. Along with our previously reported redox-responsive membranes, this article explores the mechanisms behind nonporous, stimuli-responsive ion exchange membranes. Understanding different strategies to manipulate the transport properties of dense ion exchange membranes will allow these membranes to explore capabilities such as integrated sensors, actuators, and drug delivery systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was observed that the water uptake of the samples increased as the cycle number increased, which further supported this hypothesis. Along with our previously reported redox-responsive membranes, this article explores the mechanisms behind nonporous, stimuli-responsive ion exchange membranes. Understanding different strategies to manipulate the transport properties of dense ion exchange membranes will allow these membranes to explore capabilities such as integrated sensors, actuators, and drug delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although less studied, nonporous ion exchange membranes are also possible platforms to present reversible or “switchable” transport properties in the presence of an external stimulus . Our group has previously developed redox-responsive anion exchange membranes by incorporating viologen as the anion carrier and stimuli-responsive group . Viologen undergoes a reversible conversion between two oxidation states, in which the charge of the ionic moiety changes from +2 in the oxidized state to +1 in the reduced state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanical support structures increase the composite membrane thickness, thereby reducing flux and limiting efficiency. In response to this challenge, freestanding semi‐IPNs have been prepared using a highly charged first network, often with an arylene backbone, and a rigid, second network, usually crosslinked or coordinated to the first 5–7,28–34 . While these materials have provided relatively low water content (<50 wt%) and high ion exchange capacity (IEC >1 mmol/g), they often exhibit low strains at break, and high Young's moduli.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this challenge, freestanding semi-IPNs have been prepared using a highly charged first network, often with an arylene backbone, and a rigid, second network, usually crosslinked or coordinated to the first. [5][6][7][28][29][30][31][32][33][34] While these materials have provided relatively low water content (<50 wt%) and high ion exchange capacity (IEC >1 mmol/g), they often exhibit low strains at break, and high Young's moduli. Alternatively, DNHs with reduced water content (~44 wt% water 35,36 ) have been reported, yet they lack strongly disassociating fixed charge groups, while DNHs with the requisite ion exchange groups have only been reported down to ~75-80 wt% water.…”
mentioning
confidence: 99%